Pelatihan Pemanfaatan Limbah Kain Perca Broklat bagi KWT “Mawar Putih” Karangploso – Malang - Diah Widiawati; Dyah Setyawati; Lilik Kustiani; Kurnia Isnuwardiati (IKIP PGRI Bojonegoro, 2022)
This community service aims to provide knowledge to the “Mawar Putih” women Farmer's community (KWT”Mawar Putih”) on how to utilize brocade patchwork waste, which is an inorganic waste that is difficult to decompose by the environment, into a product that has a higher economic value. This community service activity was carried out in a women farmer group located in Ngenep Village, Karangploso, Malang Regency. The implementation method carried out in this service activity starts from field visits or observations to find out partners’ problems and offer solutions, providing knowledge to women community about the importance of using brocade patchwork waste so that it has a higher economic value and efforts to protect the environment and product manufacturing practices. The results of this training activity show that women of KWT